Gambling-Related Intimate Partner Violence Against Women: A Grounded Theory Model of Individual and Relationship Determinants. Issue 19 (October 2022) - Hing, Nerilee; O'Mullan, Catherine; Nuske, Elaine; Breen, Helen; Mainey, Lydia; Taylor, Annabel; Greer, Nancy; Jenkinson, Rebecca; Thomas, Anna; Lee, Jamie; Jackson, Alun
This study aimed to examine how problem gambling interacts with gendered drivers of intimate partner violence (IPV) against women to exacerbate this violence. Interviews were conducted with 48 female victims of IPV linked to a male partner's gambling; 24 female victims of IPV linked to their own gambling; and 39 service practitioners from 25 services. Given limited research into gambling-related IPV, but a stronger theoretical base relating to IPV against women, this study used an adaptive grounded theory approach. It engaged with existing theories on gendered drivers of violence against women, while also developing a grounded theory model of individual and relationship determinants based on emergent findings from the data. Gambling-related IPV against women was found to occur in the context of expressions of gender inequality, including men's attitudes and behaviors that support violence and rigid gender expectations, controlling behaviors, and relationships condoning disrespect of women. Within this context, the characteristics of problem gambling and the financial, emotional and relationship stressors gambling causes intensified the IPV. Alcohol and other drug use, and co-morbid mental health issues, also interacted with gambling to intensify the IPV. Major implications. Reducing gambling-related IPV against women requires integrated, multi-level interventions that reduce both problem gambling and gendered drivers of violence. Gambling operators can act to reduce problem gambling and train staff in responding to IPV. Financial institutions can assist people to limit their gambling expenditure and families to protect their assets. Service providers can be alert to the co-occurrence of gambling problems and IPV and screen, treat, and refer clients appropriately. Public education can raise awareness that problem gambling increases the risk of IPV. Reducing gender inequality is also critical.